2017
DOI: 10.1186/s12936-017-1794-z
|View full text |Cite
|
Sign up to set email alerts
|

Spatial clustering and risk factors of malaria infections in Bata district, Equatorial Guinea

Abstract: BackgroundThe transmission of malaria is intense in the majority of the countries of sub-Saharan Africa, particularly in those that are located along the Equatorial strip. The present study aimed to describe the current distribution of malaria prevalence among children and its environment-related factors as well as to detect malaria spatial clusters in the district of Bata, in Equatorial Guinea.MethodsFrom June to August 2013 a representative cross-sectional survey using a multistage, stratified, cluster-selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Early studies in Choma District, Zambia found that ownership of cattle reduced the risk of P. falciparum infection by 87% while others have found less conclusive evidence [36,37]. For elevation, however, it has been clearly shown that increased elevation offers protection against malaria infection [13,20,24,26,38]. Since index and secondary households in this study were located only <300 metres from each other and variation in elevation was minimal, it is unlikely that the elevation would influence malaria risk at this spatial scale.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Early studies in Choma District, Zambia found that ownership of cattle reduced the risk of P. falciparum infection by 87% while others have found less conclusive evidence [36,37]. For elevation, however, it has been clearly shown that increased elevation offers protection against malaria infection [13,20,24,26,38]. Since index and secondary households in this study were located only <300 metres from each other and variation in elevation was minimal, it is unlikely that the elevation would influence malaria risk at this spatial scale.…”
Section: Discussionmentioning
confidence: 58%
“…During the dry season, as water accumulates into smaller pools, they become ideal larval development sites. These streams can also serve as important markers for nearby areas with similar high water table harbouring larvae [13,26,38,44]. And as these streams can be challenging to locate depending on size and season, spatial risk maps with topographical measures, such as CI and TWI, can offer guidance to CHWs to possibly reach clusters of asymptomatic carriers otherwise missed during regular RCD screening.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 For elevation, however, it has been clearly shown that increased elevation offers protection against malaria infection. 13,20,24,26,38 Since index and secondary households in this study were located only <300 meters from each other and variation in elevation was minimal, it is unlikely that the elevation would influence malaria risk at this scale. Distance from the index household marginally increased the probability of finding positive secondary households (OR: 1.24, 95% CI: 0.98 -1.58), in contrast to other studies.…”
Section: Discussionmentioning
confidence: 99%
“…26 Running head: Improving efficiency of reactive case detection Although no associations were found with the other environmental risk factors such as distance to main road, elevation, season, and number and presence of animal pens, non-parametric comparisons between positive and negative secondary households exhibited a trend of increased malaria risk for these risk factors. 19,20,21,26,36,37,38 The risk associated with animal pens varies in the literature depending on vector behavior. An.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation